Kemampuan Siswa SMP Dalam Menyelesaikan Masalah Open-Ended Berdasarkan Aspek Fluency, Flexibility, Dan Novelty - Anisa Dewi; Teguh Wibowo; Isnaeni Maryam (International Forum of Researchers and Lecturers, 2023)
This study aims to describe students' ability to solve open-ended problems based on aspects of fluency, flexibility, and novelty. This type of research is qualitative. The subject taking technique in this study was purposive. The instruments that the researchers used were open-ended tests and interview guides. The research subjects were 3 students of SMP Negeri 2 Puring class VIII for the 2021/2022 academic year who had high abilities. The data collection technique used is in the form of test sheets in the form of circle questions, field notes, interviews, and documentation. The data analysis technique used is the analytical technique from Miles & Huberman which includes three activities, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that students with high abilities have a level of creative thinking 3 (creative). Students with high abilities in solving circle problems can fulfill two of the three indicators that the researcher used. The indicators are fluency and flexibility. Fluency indicators are shown by students being able to answer questions fluently and correctly. The indicator of flexibility (flexibility) is shown by students being able to answer questions with more than one way of solving.